2017
DOI: 10.24842/1611/0037
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Attendance Registration System based Mobile Cloud Computing

Abstract: the aim of this paper is to discuss the implementation and designing an automatic attendance registration system based Mobile Cloud Computing. A prototype for managing and control the registration of student attendance is developed using Phone Gap and jQuery mobile framework. However, the mobile app is designed to help students for checking their presence details, such as the number of missed classes, and the percentage of absence. Automate the process of registering students' attendance using Bluetooth techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…The system may scan through a lot of satellite footage for interesting things or infrastructure by combining evaluations with a detecting component. It could address the initial issues in this way (Sara et al, 2019;Al-Hatmi & Yousif, 2017). Jog Sayali et al,A study comparing various supervised classifiers found that The maximum likelihood classifier demonstrates superior performance in terms of accuracy and kappa coefficient when compared to the minimum distance and parallelepiped classifiers ( Yousif M., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The system may scan through a lot of satellite footage for interesting things or infrastructure by combining evaluations with a detecting component. It could address the initial issues in this way (Sara et al, 2019;Al-Hatmi & Yousif, 2017). Jog Sayali et al,A study comparing various supervised classifiers found that The maximum likelihood classifier demonstrates superior performance in terms of accuracy and kappa coefficient when compared to the minimum distance and parallelepiped classifiers ( Yousif M., 2023).…”
Section: Introductionmentioning
confidence: 99%
“…A confirmation plan can keep unapproved clients from getting to medication data frameworks. The new advancement in the area of services and computing offers to deliver hosted services over the worldwide using public or private online cloud services [4,5]. The idea of cloud computing can be established in many levels of implementation based on the type of problem.…”
Section: Introductionmentioning
confidence: 99%